Uhakiki wa tamthilia : historia na maendeleo yake - Wafula, Richard M. (Nairobi, Kenya : Jomo Kenyatta Foundation, 1999)
History and development of Kiswahili drama.
Includes bibliographical references (p. 190-199) and index.
In Swahili.
Keywords: Swahili drama -- History and criticism; Kiswahili drama